External Diseconomies in Competitive Supply: Comment - Nichols, Alan L. (American Economic Review, 1973)
Recently in this Review, Charles Goetz and James Buchanan advanced the proposition that output-generated external diseconomies may be associated with a production possibilities curve internal to an attainable curve and that under competition it would be the former on which equilibrium would occur. This in turn they take to imply that the conventional tax-bounty analysis offers, in general, an incorrect remedy in that it applies to the wrong production possibilities curve. The present discussion does not deny that the results indicated by Goetz and Buchanan occur, as they too note, in the context of input-generated external diseconomies nor that their results may be conceivable in the context of output generated external diseconomies.' We do however denv that the analytical structure they offer in support of their conclusion is admissible. The analytical case Goetz and Buchanan make is, in terms of Dean Worcester's classification, that of Externalities which are internal to a specific (p. 884). They employ the crucial specification, on which their results turn, that the costs of each firm (where firms are identical) depend on a function which includes the output of other firms, as distinct from total industry output, as an argument. Where ci, qi, Qi are, respectively, firm total cost, firm total output, and output of all other firms corresponding to any particular firm, i, we have